The representational instability in the generalization of fear learning - Kenny Yu; Wolf Vanpaemel; Francis Tuerlinckx; Jonas Zaman (npj Science of Learning)
Abstract Perception and perceptual memory play crucial roles in fear generalization, yet their dynamic interaction remains understudied. This research (N = 80) explored their relationship through a classical differential conditioning experiment. Results revealed that while fear context perception fluctuates over time with a drift effect, perceptual memory remains stable, creating a disjunction between the two systems. Surprisingly, this disjunction does not significantly impact fear generalization behavior. Although most participants demonstrated generalization aligned with perceptual rather than physical stimulus distances, incorporating perceptual memory data into perceptual distance calculations did not enhance model performance. This suggests a potential shift in the mapping of the perceptual memory component of fear context, occurring alongside perceptual dynamics. Overall, this work provides evidence for understanding fear generalization behavior through different stimulus representational processes. Such mechanistic investigations can enhance our understanding of how individuals behave when facing threats and potentially aid in developing mechanism-specific diagnoses and treatments.